2022
DOI: 10.3390/ijms23052536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Dichotomous Procoagulant COAT Platelet Generation—A Conceptual Review Summarizing Current Knowledge

Abstract: Procoagulant platelets are a subtype of activated platelets that sustains thrombin generation in order to consolidate the clot and stop bleeding. This aspect of platelet activation is gaining more and more recognition and interest. In fact, next to aggregating platelets, procoagulant platelets are key regulators of thrombus formation. Imbalance of both subpopulations can lead to undesired thrombotic or bleeding events. COAT platelets derive from a common pro-aggregatory phenotype in cells capable of accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 247 publications
(467 reference statements)
0
6
0
Order By: Relevance
“…The current literature proposes that the development of platelet subpopulations may be based on a spectrum of activation, depending on the strength of stimulation and the cytoplasmic calcium concentration 57 , 58 . It has also been suggested that procoagulant and apoptotic platelets may be interrelated 24 , 25 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The current literature proposes that the development of platelet subpopulations may be based on a spectrum of activation, depending on the strength of stimulation and the cytoplasmic calcium concentration 57 , 58 . It has also been suggested that procoagulant and apoptotic platelets may be interrelated 24 , 25 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with a previous report by Alberio’s group describing a high proportion of COAT platelets within the TO bright population [ 16 ]. To become procoagulant, a high and sustained intracytopasmic calcium rise is required to externalize PS and bind coagulations factors [ 3 , 17 ]. Because platelet aging has been reported to be linked to a decrease in cytoskeletal protein, mitochondrial number, and calcium dynamics [ 18 ], it could represent one of the mechanisms explaining the propensity of young platelets to become procoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…Procoagulant or COAT (COllagen And Thrombin activated) platelets are activated platelets exposing negatively charged aminophospholipids and binding several α -granular proteins including factor V and von Willebrand factor (vWF), which cluster together to form a coat [ 2 ]. Approximately one-third of platelets become procoagulant after stimulation, but this predisposition is still under debate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depolarization is associated with permeabilization of the mitochondrial membrane and causes a spike in cytoplasmic calcium which can, in turn, lead to depolarization of adjacent mitochondria 10 . When the density of mitochondria within the platelet is increased, this would be predicted to enable more efficient propagation of calcium flux to adjacent mitochondria 27 . Consistent with this hypothesis, thrombin hypersensitivity to depolarization was most marked in the cohort of patients with ET (versus PV) in whom mitochondrial mass showed the greatest increase.…”
Section: Discussionmentioning
confidence: 99%